Disseminated Intravascular Coagulation: Clinical Spectrum and Established as well as New Diagnostic Approaches - Müller-Berghaus, Gert; ten Cate, Hugo; Levi, Marcel (Thrombosis and Haemostasis, 1999)
Although disseminated intravascular coagulation (DIC) is an “intermediary mechanism of disease”1 that has been intensively studied during the last three decades,2-4 several aspects relating to the clinical problem of DIC are still under debate. For example, a standardized definition of disseminated intravascular coagulation has not yet been agreed upon. A diagnosis can be accurately made using the facilities of a specialized laboratory, but time constraints make the diagnosis of DIC by the general laboratory difficult. Since DIC can be prevented if the right therapy is initiated early, the ability to quickly and accurately diagnose DIC and to monitor the involved dynamic processes are essential prerequisites for the effective management patients with DIC.Due to the problems associated with defining DIC, making an early diagnosis, and effectively treating the condition following diagnosis, the clinical management of DIC can be difficult. The transition from an activated hemostatic system to a well-defined state of DIC is indistinct, and the borderlines cannot easily be distinguished. In addition, different underlying diseases mediating DIC induce different clinical symptoms associated with DIC and demand different therapeutic approaches.